Pressure and traction on a model fetal head and neck associated with the use of forceps, Kiwi™ ventouse and the BD Odon Device™ in operative vaginal birth: a simulation study. (21st September 2017) - O'Brien, SM; Winter, C; Burden, CA; Boulvain, M; Draycott, TJ; Crofts, JF
Abstract : Objective: To determine the pressure and traction forces exerted on a model fetal head by the BD Odon Device, forceps and Kiwi ventouse during simulated births. Design: Simulation study. Setting: Simulated operative vaginal birth. Population or sample: Eighty‐four simulated operative vaginal births. Methods: A bespoke fetal mannequin with pressure sensors around the head and strain gauge across the neck was used to investigate pressure applied over the head, and traction across the neck during 84 simulated births using the BD Odon Device, non‐rotational forceps and Kiwi ventouse. Main outcome measures: Peak pressure on the fetal face and lateral aspects of the head during correct use of the BD Odon Device and forceps. Peak pressure on orbits and neck during misplacement of the BD Odon Device and forceps. Peak traction force generated until instrument failure using the BD Odon Device, forceps and Kiwi ventouse. Results: When correctly sited and using 80 kPa inflation pressure on the cuff, the BD Odon Device generated a lower peak pressure on the fetal head than forceps (83 versus 146 kPa). When instruments were purposefully misplaced over the orbits, the BD Odon Device generated a lower peak pressure on the orbits compared with forceps (70 versus 123 kPa). When purposefully misplaced over the neck, the BD Odon Device, compared with forceps, generated a greater peak pressure on the anterio‐lateral aspect of the neck (56 versus 17 kPa) and a lower peak pressure on the posterior aspect of the neck (76 versus 93 kPa) than forceps. In cases of true cephalic disproportion, the BD Odon Device 'popped‐off' at a lower traction force than did forceps (208 versus 270 N). Conclusions: In simulated assisted vaginal birth with correctly placed instruments, the peak pressure exerted on the fetal head by a BD Odon Device is lower than the pressure exerted by non‐rotational forceps. In cases in which delivery of the fetal head is not possible due to cephalo‐pelvic disproportion, lower traction forces could be applied using the BD Odon Device than with forceps before the procedure was abandoned due to device failure. Tweetable abstract: BD Odon Device exerts less pressure on a model fetal head than forceps, but more than Kiwi ventouse. Tweetable abstract: BD Odon Device exerts less pressure on a model fetal head than forceps, but more than Kiwi ventouse.